Spin‐resolved charge density and wavefunction refinements using MOLLYNX: a review. Issue 5 (24th September 2021) - Souhassou, Mohamed; Kiblin, Iurii; Deutsch, Maxime; Voufack, Ariste Bolivar; Lecomte, Claude; Claiser, Nicolas
Abstract : This article describes the joint refinement program MOLLYNX dedicated to spin‐resolved electron density distribution. Multipole and atomic orbital models are described and applications for organic and inorganic magnetic materials are discussed. Abstract : MOLLYNX is a new crystallographic tool developed to access a more precise description of the spin‐dependent electron density of magnetic crystals, taking advantage of the richness of experimental information from high‐resolution X‐ray diffraction (XRD), unpolarized neutron (UND) and polarized neutron diffraction (PND). This new program is based either on the well known Hansen–Coppens multipolar model ( MOLLYNX ‐mult) or on a new expansion over a set of atomic orbitals ( MOLLYNX ‐orb). The main difference between the two models is the basis of the expansion: in MOLLYNX ‐mult the expansion is over atom centered real spherical harmonics, in MOLLYNX ‐orb the expansion is over a set of atomic orbitals with which mono and bicentric contributions are calculated. This new approach of MOLLYNX ‐orb can also be applied to nonmagnetic crystals. This paper summarizes the theoretical ground of two models and describes the first applications to organic, organometallic and inorganic magnetic materials